Some degree-based topological indices of triphenylene polyester - Muge Togan; Aysun Yurttas Gunes; Musa Demirci; Ismail Naci Cangul (Indonesian Journal of Combinatorics, 2021)
Molecules can be modelled by graphs to obtain their required properties by means of only mathematical methods and formulae. In this paper, several degree-based graph indices of one of the important chemical compounds called as polyester are calculated to determine several chemical and physicochemical properties of polyester.